Assessment on the incidence of notifiable infectious diseases in pediatrics post-COVID-19: a retrospective study based on data from 2020 to 2023 - Sun, Wei; Luo, Zujin; Li, Shunli; Zhu, Hongbin; Ma, Yingmin; Wang, Jing (Frontiers in Pediatrics, 2025)
Background and aimThe Coronavirus Disease 2019 (COVID-19) pandemic has notably affected pediatric health, especially regarding notifiable infectious diseases. While strict control measures reduced infection transmission, they also lowered herd immunity, possibly causing a rise in pediatric infectious disease cases once restrictions were eased. The aim of the study is to compare the number of pediatric outpatient and emergency visits and the incidence rates of notifiable infectious diseases from 2020 to 2023.MethodsWe retrospectively analyzed pediatric department visit cases from 2020 to 2023 and compared variations in the number and proportion of notifiable infectious diseases across different years.ResultsOur findings revealed a sharp increase in pediatric visits, from 31,401 before the pandemic to 89,945 in 2023, representing an approximate threefold increase. Notifiable infectious disease cases rose from 224 in 2020 to 1027 in 2023, marking an increase of nearly 4.6 times. The incidence of influenza, hand-foot-mouth disease (HFMD), and infectious diarrhea also markedly increased.ConclusionsThese findings establish a significant association between the relaxation of COVID-19 restrictions and increased pediatric infectious disease occurrence. In 2023, there has been a substantial increase in the number of pediatric outpatient and emergency department visits, as well as in the incidence rate of notifiable infectious diseases, when compared to the period from 2020 to 2022. Notably, the incidence of influenza has exhibited the most pronounced increase, while the incidence rates of measles and mumps have remained stable.